As ações afirmativas como instrumento de inclusão social: uma análise à luz da teoria da igualdade de recursos de Ronald Dworkin - VALENTE, Karla Rafaelli Ribeiro (Universidade Federal do Pará, 2017)
This study intends to discuss affirmative action as able instruments to promote the social inclusion of vulnerable groups, specifically black people. We try to justify the use of affirmative actions by the State from the perspective of distributive justice, from the conception of the theory of “equality of resources”, developed by c. To justify the use of these measures, we set from the Dworkin's liberal political theory, trying to analyze the values that comprise it, whice are: liberty, equality and community. Inside this discussion of the justification for affirmative action, we established that they should be guided by the criteria of justice, adequacy and efficiency, under penalty of being unconstitutional and innocuous. We understand that this discussion fits perfectly to the Brazilian reality, which is marked by profound social exclusion. Furthermore, any analysis of the substantive content of equality needs take place in the context of a “normative political theory”. That’s why we choose to study this question from Dworkin's theory, which is consistent with the precepts contained in CRFB/1988. After forming this fundamental basis, we start to analyze the case in Brazil, taking as a paradigm the policy adopted by UFPA through Resolution nº. 3.361/2005/CONSEP, investigating whether the measure adopts the minimum retro-mentioned criteria.